Leitura intersemiótica de O Homem Duplicado de Saramago e sua adaptação cinematográfica Enemy de Villeneuve – Um estudo comparativo - Silva, Clara Maria (CEM – Cultura, Espaço & Memória, 2020)
While adopting an intersemiotic perspective, José Saramago’s work O Homem Duplicado (2002) will be analysed altogether with its cinematographic adaptation Enemy (2013) by Denis Villeneuve. The latter work constructs a thematic reformulation provided by the narrative that encircles and circumscribes it. Thus, the writing of a filmic text results in its independence. We ought to understand how the thematic construction recodes Saramago’s work, culminating in the opening of a debate on the fidelity principle designed by cinematographic thinkers such as André Bazin.